Review papers immunosuppressive treatment - Anna Kryś; Beata Imko-Walczuk; Sławomir Lizakowski; Alicja Dębska-Ślizień; Bolesław Rutkowski; Wojciech Biernat (Termedia Publishing House, 2014)
Sebaceous carcinoma (sebaceous gland carcinoma - SC) is a very aggressive malignant skin tumor that arises from the epithelium of sebaceous glands. Sun exposure and long-term immunosuppression, mainly in organ transplant recipients, are the most common risk factors. The tumor was first well described by Allaire in 1891. Sebaceous carcinoma is rare and accounts for less than 1% of all cutaneous malignancies and from 1% to 5.5% of all eyelid malignancies. The most common localization is the eyelids, where it derives from the Meibomian and Zeiss glands. Most cases occur in woman between 60 and 80 years of age, but the tumor can be seen at any age, even in childhood. It appears mostly as a small, slowly growing, painless and firm mass, sometimes as a small yellowish plaque or ulceration. SC has a tendency for local recurrence and distant metastases. The local recurrence rate ranges from 9 to 36% and tends to appear within the first 5 years from diagnosis. The most effective method of treatment is surgical excision (Mohs' microsurgical excision if it is possible). The rate of metastases is about 14-25%. The sites of metastases are usually lymph nodes, liver, lungs, bones, and brain. The mortality rate is about 22% but it increases to 50% at 5 years in patients with metastatic disease.